P-100 ANATOMICAL STUDY ON THE PREPERITONEAL FAT DISTRIBUTION IN EXTENDED RETROMUSCULAR PREPERITONEAL DISSECTION: FROM THE FATTY TRIANGLE TO THE FATTY TRIDENT. (13th October 2022) - Garcia-Urena, M A; Lopez-Monclus, J; Medina, M; Aviles, A; Blazquez Hernando, L A; Robin Valle De Lersundi, A; Munoz-Rodriguez, J; Rial, X; Minaya, A; Sanchez, A
Abstract: Aim: Extended retromuscular dissection performed for abdominal wall reconstruction in complex abdominal wall repair has progressively exposed the anatomy between the peritoneal layer and abdominal wall muscles. This study aimed to assess the morphology and distribution of preperitoneal fat in a cadaveric model. Material and methods: Thirty frozen cadaver torsos were dissected by posterior component separation. The shape of the preperitoneal fat was identified, and the dimensions and more significant distances were calculated. Results: The results showed that the preperitoneal fat resembles a trident, exists along the midline under the linea alba, and expands in the epigastric area into a rhomboid shape. The fatty triangle was found to be a part of this rhomboid. The mean rhomboid area was 35 cm 2 . Caudally, the midline preperitoneal fat widened under the arcuate line to reach the Retzius space. Laterally, the Bogros space communicated the root of the trident with the paracolic gutters, Toldt's fascia, and pararenal fats, forming the lateral prong of the trident. The mean width of the midline prong at the umbilicus was 2.8 cm. It was easier to tear the peritoneum outside the area reinforced by the fatty trident. Conclusions: The concept of preperitoneal fatty trident may be of practical assistance to perform various hernia procedures, from the simple ventral hernia repair to the more complex preperitoneal ventral repair or posterior component separation techniques. The consistency of this layer allows us to follow our plane between the peritoneum and muscle layers to extend the preperitoneal dissection.